Legal Review of Investment Implementation In Vietnam and In Indonesia Is Reviewed Based On Investment Regulations In Each Country - Alifio Izza Dhesta (Asian Journal of Social and Humanities, 2024)
Investment or investment is an activity to increase the capital owned by a company or country with the aim of earning profits in the future. This activity is carried out by investors both from within the country and abroad, having a positive impact on Indonesia's economic development. The purpose of this study is to analyze the implementation of investment in Indonesia and Vietnam, especially related to regulations in each country. In addition, the study also aims to identify the advantages and disadvantages of foreign investment in both countries. Descriptive legal research methods and comparative approaches are used to analyze the implementation of investment in Indonesia and Vietnam, focusing on investment regulations, advantages, and disadvantages of each country. The results of the study show that although Indonesia has natural potential, political stability, and strong government support, the country is still less attractive than Vietnam in terms of Foreign Investment (FDI). Vietnam has managed to attract more foreign investment thanks to more investor-friendly regulations and better legal certainty. In conclusion, to increase competitiveness in attracting foreign investment, Indonesia needs to improve investment regulations and create a more conducive investment climate.